The Role of Education for Children with Intellectual Disabilities at SLB-C Beringin Bhakti - Wawa Tilawatila; Chaerul Rizki; Rita Purnamasari (CV. Akademi Merdeka, 2024)
Education is essential for one's current and future success. Education provides a wealth of facts and knowledge that will improve a person's life and behavior. Everyone regardless of status, religion, ethnicity, race, or membership in a particular group, is entitled to a good education. Formal education is education that is carried out through education in schools. Non-formal education is an educational path that is carried out outside of formal education. Children with special needs (ABK) are entitled to education. Children with special needs have different characteristics from children who suffer from mental, emotional, or physical illnesses in general. Education for children with special needs has many benefits for children. The problem in this study is the lack of educational attention for friends with disabilities. Therefore, this study aims to find out how education for visually impaired children and to improve SLB education as a learning home for these children. This research method uses descriptive qualitative research. This research method aims to describe the phenomenon or event that is being studied in an in-depth and detailed way. The data collection technique is by means of observation of the research field, collecting data, interviews, and documentation.